PENINGKATAN NILAI TAMBAH PENGRAJIN DUPA DESA PETUNGSEWU KECAMATAN WAGIR KABUPATEN MALANG - Sarwoko, Endi; Nurdiana, Iva; Ahsan, Mohammad (UNIVERSITAS PGRI MADIUN, 2019)
Abstract, Petungsewu Village, Wagir District, Malang Regency is one of the villages where most of the people are incensed craftsmen, but the incense produced is semi-finished incense or raw incense. The problem faced by incense craftsmen is that the selling price of semi-finished incense tends to decline from year to year, the limited bamboo raw material even has to be imported from other areas, only producing semi-finished incense (raw). The aim of the activity is to increase the value added of incense products, and increase people's income by selling incense products with brand packaging. The method of implementing the activity is to diversify the product by training and mentoring in making incense, product packaging training and quality control, online marketing training, utilizing incense making technology. As a result of community service activities, the community is able to produce fragrant incense packaged and branded and has been sold. Besides that, by utilizing incense bamboo making technology, the production capacity of incense biting production increased, the quality of the bamboo produced was more uniform, so the problem of limited incense material could be overcome.Keywords: Craftsmen, Value Added, Training Abstrak, Desa Petungsewu Kecamatan Wagir Kabupaten Malang adalah salah satu desa yang sebagian besar masyarakatnya adalah pengrajin dupa, tetapi dupa yang dihasilkan adalah dupa setengah jadi atau dupa mentah. Permasalahan yang dihadapi para pengrajin dupa adalah harga jual dupa setengah jadi cenderung turun dari tahun ke tahun, keterbatasan bahan baku biting bahkan harus didatangkan dari di daerah lain, hanya memproduksi dupa setengah jadi (mentah). Tujuan kegiatan pengabdian ini adalah untuk meningkatkan nilai tambah produk dupa, dan peningkatan pendapatan masyarakat dengan menjual produk dupa jadi dengan kemasan merek. Metode pelaksanaan kegiatan adalah melakukan diversifikasi produk dengan pelatihan dan pendampingan membuat dupa wangi, pelatihan pengemasan produk dan quality control, dan pelatihan pemasaran online, pemanfaatan teknologi pembuatan biting dupa. Hasil kegiatan pengabdian, masyarakat mampu menghasilkan dupa wangi yang dikemas dan diberi merek dan sudah mulai dijual. Selain itu dengan pemanfaatan teknologi pembuatan biting dupa, kapasitas produksi pembuatan biting dupa meningkat, kualitas biting yang dihasilkan lebih seragam, sehingga permasalahan keterbatasan bahan biting dupa dapat diatasi.Kata Kunci: Dupa Wangi, Nilai Tambah, Pelatihan